The Concept of "Mabbalu Nabi" Among Traders of Bugis Bone: : an Analysis of The Motives and Its Relevance to The Principles of The Prophet's Trade - Abdulahanaa hana (Al-Ulum, 2020)
Bugis Bone traders have a term known as "mabbalu' nabi." The term meaning is identified with "mabbalu’ nabi” because the goods are sold at a capital price or even below, then the term "mabbalu' prophet" is a term of sale and purchase that does not include concern profit (profit). Such a concept of buying and selling is irrelevant to the motives of buying and selling in economics. This problem has never been investigated by researchers before. This study is the first study to examine the conception, motives, implementation, and relevance of the term "mabbalu’ nabi” version of the Bugis Bone merchants with the Prophet's trade principles. The results showed that the conceptions and motives of the "mabbalu’ nabi” by Bugis Bone traders varied. Some were in line, and some were out of the Prophet Saw's trading principles consistent professional trader who did not confuse business affairs with afterlife affairs.